Love and eroticism - Featherstone, Mike. (London ; Thousand Oaks, Calif. : Sage, 1999)
Exploring the contested nature of love and eroticism, this collection examines the ways in which erotic bodily pleasures have become central to contemporary consumer culture.
Machine derived contents note: Love and Eroticism -- Mike Featherstone -- An Introduction -- On the Postmodern Uses of Sex -- Zygmunt Bauman -- The Sexual Citizen -- Jeffrey Weeks -- On the Way to the Post-Familial Family -- From a Community of Need to Elective Affinities -- Elizabeth Beck-Gernsheim -- On the Elementary Forms of Socioerotic Life -- Sasha Weitman -- Bohemian Love -- Elizabeth Wilson -- Otto Gross and Else Jaff[ac]e and Max Weber -- Sam Whimster with Gottfried Heuer -- The Lost Innocence of Love -- Eva Illouz -- Romance as a Postmodern Condition -- Balancing Sex and Love since the 1960's Sexual Revolution -- Cas Wouters -- Citysex -- Henning Bech -- Representing Lust in Public -- Love and Structure -- Charles Lindholm -- `Falling in Love with Love is Falling for Make Believe' -- Mary Evans -- Ideologies of Romance in Post-Enlightenment Culture -- Introduction to Georg Simmel's 'On the Sociology of the Family' -- David Frisby -- On the Sociology of the Family -- Georg Simmel -- Sex and Sociality -- Laura Rival, Don Slater and Daniel Miller -- Comparative Ethnographies of Sexual Objectification -- The Nazi Eye Code of Falling in Love -- Andrew Travers -- Bright Eyes, Black Heart, Crazed Gaze -- `On Me, Not In Me' -- Cindy Patton -- Locating Affect in Nationalism after AIDS -- Seductions of the Impossible -- Michael Richardson -- Love, the Erotic and Sacrifice in Surrealist Discourse -- The Lesson of Fire -- Maria Esther Maciel -- Notes on Love and Eroticism in Octavio Paz's /f003The Double Flame -- Love, Gender and Morality -- Mike Hepworth -- Stephen Kern's `Eyes of Love' -- Bodies, Sex and Death -- Arthur W Frank.
Simultaneously published as Volume 15, Numbers 3-4 of 'Theory, Culture & Society' - title page verso.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Sex customs; Love; Love; Vie sexuelle; Amour; love (emotion); PSYCHOLOGY -- Human Sexuality; SELF-HELP -- Sexual Instruction; Love; Sex customs; Seksualiteit; Liefde; Erotiek; Amour; Érotisme.; Vie sexuelle